SENGKETA PENGELOLAAN KAWASAN TAMAN NASIONAL DALAM ERA OTONOMI DAERAH (Kasus Taman Nasional Kutai Kalimantan Timur) - Sudiyono Sudiyono (LIPI Press, 2005)
This study is focussed on the conflict authority among the central government vs local government to manage forest conservation of Kutai Forest National Park (Taman Nasional Kutai), under the District Kutai Timur Government. Through this study have been identified many factors caused conflict; (1) inconsistency of the policy government, as well as showed in the regulations nature resource management, especially on the forest.(2)weakness of the outhority holders (Balai Taman Nasional Kutai). (3) increasingly of the public participation on the activities development on all of these levels in the Regional Autonomy Era (4) increasingly interest of the stakeholders to land utilization in the forest national park. As implication of the conflict interest are occurred forest destruction can not be hinderance.